Comparison of Pediatric Sequential Organ Failure Assessment and Pediatric Risk of Mortality III Score as Prediction in Pediatric Intensive Care Unit - Khan, Kashmala; Shakoor , Ibrahim; Um e Aiman; Kausar , Narmeen; Abdul Ghaffar, Tooba; Azeem, Yusra (Indus Journal of Bioscience Research, 2025)
Objective: To compare the predictive accuracy of Pediatric Sequential Organ Failure Assessment (pSOFA) and Pediatric Risk of Mortality III (PRISM III) scores for mortality prediction in children admitted to the pediatric intensive care unit. Study Design: Prospective longitudinal study. Place and Duration of Study: Pediatric Intensive Care Unit, Abbasi Shaheed Hospital, Karachi, from June 2024 to January 2025. Methodology: A total of 207 critically ill children aged between 1 month and 12 years who remained in the PICU for at least 24 hours were enrolled using non-probability consecutive sampling. PRISM III and pSOFA scores were calculated within the first 24 hours of PICU admission. Patients were followed until discharge from the PICU, and 30-day mortality was recorded as the primary outcome. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated for both scoring systems. Results: The mean age of the patients was 4.9 ± 3.6 years and 118 (57.0%) were males. Overall mortality was observed in 43 (20.8%) patients. The mean PRISM III score was significantly higher in non-survivors compared with survivors (19.7 ± 6.3 vs. 11.2 ± 4.6). Similarly, the mean pSOFA score was higher among non-survivors compared with survivors (9.6 ± 3.1 vs. 5.1 ± 2.2). The pSOFA score demonstrated higher sensitivity (83.7%) and specificity (78.0%) compared with PRISM III (79.1% and 74.4%, respectively). The area under the receiver operating characteristic curve was 0.82 for pSOFA and 0.76 for PRISM III. Conclusion: Both PRISM III and pSOFA scores are useful tools for predicting mortality in critically ill children admitted to the PICU; however, pSOFA demonstrated better predictive performance. The pSOFA score may therefore serve as a practical and reliable scoring system for mortality prediction in pediatric intensive care settings.